2009
DOI: 10.1016/j.vetmic.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for the presence of ruminant pestiviruses in the Dutch swine population

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 tests. The presence of BVDV and BDV in a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 33 publications
(1 reference statement)
5
57
1
Order By: Relevance
“…Similar results, i.e. higher rate of BVDV seroprevalence in pigs on mixed farms, was also reported by Deng et al (19), and Tao et al (38). At that time, the presence of seroreagents was found in all provinces in which the samples were collected (29).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Similar results, i.e. higher rate of BVDV seroprevalence in pigs on mixed farms, was also reported by Deng et al (19), and Tao et al (38). At that time, the presence of seroreagents was found in all provinces in which the samples were collected (29).…”
Section: Discussionsupporting
confidence: 81%
“…Studies on BVDV/BDV seroprevalence in swine are rare and mostly difficult to compare because of different sampling schemes, different age categories of tested animals, and different tests applied (19). Studies on seroprevalence of ruminant pestiviruses in wild boar were conducted in Germany (3,34), the USA (20), Croatia (31,44), and the Czech Republic (33) and revealed that the percentage of seropositive animals did not exceed 8%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations